2012
DOI: 10.1080/08856257.2012.711961
|View full text |Cite
|
Sign up to set email alerts
|

The identification of special educational needs and the month of birth: differential effects of category of need and level of assessment

Abstract: The processes around the identification of special educational needs (SEN) should mean that those pupils who need most help receive it. However, there are concerns that this process is not working and there is an over-identification of pupils with SEN. Previous international research has shown that summer-born children are more likely to be identified as having SEN. However, these studies tend to treat SEN as a homogenous group. In this paper, we explore the extent to which the month-of-birth effect can be see… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 8 publications
(9 reference statements)
0
6
0
1
Order By: Relevance
“…Although we found that more of the youngest children within cohorts scored above clinical threshold than older children, the present study was not positioned to determine how this translates into higher risk of diagnosis or need of specialist mental health treatment. However, there is evidence that the SDQ is a fairly reliable public health indicator of clinical need [31], and existing research indicates that disproportionately more of the youngest children in a school cohort are likely to be receiving psychology services and intervention [7] and special educational needs assessment [12,32].…”
Section: Study Strengths and Limitationsmentioning
confidence: 99%
“…Although we found that more of the youngest children within cohorts scored above clinical threshold than older children, the present study was not positioned to determine how this translates into higher risk of diagnosis or need of specialist mental health treatment. However, there is evidence that the SDQ is a fairly reliable public health indicator of clinical need [31], and existing research indicates that disproportionately more of the youngest children in a school cohort are likely to be receiving psychology services and intervention [7] and special educational needs assessment [12,32].…”
Section: Study Strengths and Limitationsmentioning
confidence: 99%
“…La norme incarnée par le groupe-classe constitue un autre facteur-clé influenc ¸ ant l'identification de besoins particuliers chez un élève au cours de sa scolarité, ainsi que l'ont montré précédemment d'autres études (Croll, 2002 ;Hibel et al, 2010 ;Keslair & McNally, 2009 ;Lupton et al, 2010 ;McCoy et al, 2012 ;Squires et al, 2012). Selon Dupanloup (1998), le fait de comparer l'élève à ses pairs constituerait une stratégie mise en place par les enseignants en vue de remédier au flou entourant les critères d'évaluation, mais également un « projet éducatif parfois occulté d'homogénéisation des individus en devenir que sont les enfants » (p. 53).…”
Section: Discussion Des Résultatsunclassified
“…Furthermore, less scrupulous academies engaged in covert selection procedures (Burgess et al, 2017;Rayner, 2017;Department for Education, 2018Liu et al, 2020) and 'off-rolling' became a popular school-improvement tool as growing numbers of Year 11 pupils with social, emotional and mental health (SEMH) difficulties found themselves in alternative provision with only a 10% chance of being reintegrated into mainstream settings (Squires et al, 2012;Department for Education, 2018Timpson, 2019). One Local Authority suggested alternative provision had become a de facto special school as pupils with high-incidence SEN were effectively erased from mainstream settings.…”
Section: Emergent Influence Of Whole-community Agendas On Sen Prevalencementioning
confidence: 99%
“…Ultimately, a divisive 'corporation' (Deleuze and Guattari, 1987) comprising Local Authorities, multi-agency professionals, businesses, voluntary organisations and parents had been established, all of whom had vested interests in SEN diagnosis. Moreover, the most vulnerable pupils were further disadvantaged, as social isolation and feelings of poor self-belief intensified (Squires et al, 2012;Lindsay and Strand, 2016;Rayner, 2017 'haunted' the near future (Deleuze and Guattari, 1987). Together, this highlights how SEN prevalence can be an artefact of complex interactions between and within whole-community agendas, leading to the claim that SEN prevalence increases when resources are linked with SEN diagnosis (Tomlinson, 2010(Tomlinson, , 2012Lindsay, 2018).…”
Section: Emergent Influence Of Whole-community Agendas On Sen Prevalencementioning
confidence: 99%
See 1 more Smart Citation